Reducing the digital gap in the labor market: for more e-inclusive workplaces - Badarevski, Bobi (Ревија за социјална политика/Journal of Social Policy, 2012)
The strategic document DigitalAgenda, as part of the strategy Europe 2020, determines the approach for developing the digital economy. Getting skills in ICT or digital skills necessary for innovation and development are important prerequisites for the development of a digital society. Such strategies should have as target groups the population which is the most vulnerable segment of society: in fact, persons, especially women, who would benefit the most from the use of ICT, are often people who are excluded from the opportunity to use the benefits offered by the new technologies. The study identifies the gender relations in some of the key strategic documents on ICTin the Republic of Macedonia and the European Union and from gender perspective it examines the opportunities and assumptions of the concept of “e-inclusion” for greater participation of women in the labor market, especially in the ICT sector.
Keywords: digital economy; gender; e-inclusion